SARS-CoV-2 Serology Antibody in Children with MIS-C (Multiple Inflammatory Syndrome in Children) Suspected - Finny Fitry Yani; Indra Ihsan; Efrida (HM Publisher, 2022)
Background: Multiple inflammatory syndromes in children (MIS-C) relate to COVID-19 severity in children. SARS-CoV-2 serology antibody is one of the diagnostic tools of MIS-C. The study aimed to describe the yield of serology antibodies of MIS-C and some characteristics found in hospitalized children with MIS-C suspects. Methods: This research was an analytic observational study. The data were collected retrospectively from some children who were hospitalized in Dr. M. Djamil General Hospital, Padang, West Sumatra, Indonesia, from April - June 2021. The inclusion criteria were children aged 1 month to 18 years, with or without contact history with the person who probable or confirmed COVID-19 and have signs and symptoms as MIS-C base on WHO criteria. Results: About eight out of 44 children showed positive serology antibodies and were diagnosed as MISC (18,2%). Based on demographic characteristics, children aged 11-15 years (27.3%) and boys were more affected (52.3%) as MIS-C suspected. Most of them were referred from a 2nd-level hospital outside Padang City (70.4%), but only 13.6% had a history of contact with COVID-19 confirmation patients. There was a significant difference in cardiovascular signs and symptoms between positive and negative serology antibody SARS-CoV-2 among children with MIS-C suspected (p<0.05), but not in fever, respiratory distress, gastrointestinal, neurology symptoms, either in laboratory results such as leukocytes, CRP and D-dimmer. Intravenous immunoglobulin, steroid, and PICU admitted showed no significant differences between the 2 groups, but more death prevalence in positive than negative. However, no significant differences (12.5% vs. 11.1%, p>0.05). Conclusion: Cardiovascular signs and symptoms could be proposed to be one of the significant differences in clinical conditions to differentiated children with MIS-C suspected and MIS-C due to serology antibody results.